Aspek Psikologi Pendelegasian Manajemen dan Manajemen Biaya Pabrik Roti “Yes” di UPK PIK Pulo Gadung Jakarta Timur - Hanif Hanif; Mulyani Mulyani; Supriyanto Karya; Morryessa Brandinie (ACADEMICS IN ACTION Journal of Community Empowerment, 2019)
The purpose of this program is to provide assistance in order to help businesses to solve their problems in business management. The approach used is observation, interview and discussion with the business founder/owner. The place is in the one of the business unit under the Unit Pengelola Kegiatan Pusat Industri Kecil (PIK), namely ” Yes" Cake Factory. The team managed and explored several problems in the business unit, which are related to book-keeping, work delegation and the control system planning, utilization of cost management such as unit cost calculations, cost control and break event point analysis, and profit-sharing policy. The team also provides a doable solution that can be implemented by the company.